Who cooked the last supper? eaudiobook The women's history of the world. - Miles, Rosalind (Tantor Media, 2018)
Who Cooked the Last Supper? overturns the phallusy of history and gives voice to the untold history of the world: the contributions of millions of unsung women. Men dominate history because men write history. There have been many heroes, but no heroines. Here, in Who Cooked the Last Supper? , is the history you never learned—but should have! Without politics or polemics, this brilliant and witty book overturns centuries of preconceptions to restore women to their rightful place at the center of culture, revolution, empire, war, and peace. Spiced with tales of individual women who have shaped civilization, celebrating the work and lives of women around the world, and distinguished by a wealth of research, Who Cooked the Last Supper? redefines our concept of historical reality.